PENINGKATAN MOTIVASI BELAJAR SISWA MTS MELALUI PEMANFAATAN MEDIA CANVA DALAM PEMBELAJARAN AQIDAH AKHLAK - Saputri, Eka Wulan; Azis, Achmad Abdul; Rizal, Ahmad Saiful (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This study aims to examine the implementation of Canva as a digital learning medium in teaching Aqidah Akhlak, specifically on the topic of akhlaq mahmudah, as an effort to enhance the learning motivation of ninth-grade students at MTs Miftahul Ilmiyah Mojowetan Blora. The research is grounded in the gap between the ideal expectation of Aqidah Akhlak education—which is to nurture faith and noble character and the classroom reality, where students often demonstrate low interest and limited engagement. A qualitative approach with a case study design was employed, using interviews, observations, and documentation as data collection techniques. The findings reveal that the use of Canva enables teachers to deliver akhlaq mahmudah materials through creative, interactive, and visually engaging formats such as posters, infographics, and digital presentations. This implementation effectively increased students’ learning motivation, fostered a more participatory classroom atmosphere, and facilitated the internalization of Islamic values in a more meaningful way. Nevertheless, several challenges were identified, including teachers’ limited digital competence, unequal access to digital devices among students, and technical issues such as unstable internet connectivity. On the other hand, supporting factors included teachers’ enthusiasm, students’ interest in visual-based media, and the availability of school facilities that supported the innovation. The implications of this study highlight the strategic role of digital media, particularly Canva, in promoting contextual and engaging Islamic education that resonates with the learning characteristics of the digital generation. The study recommends continuous professional development for teachers and the provision of adequate technological infrastructure. Furthermore, future research is suggested to expand the exploration of Canva in Aqidah Akhlak learning and to integrate it with other innovative technology-based instructional models to achieve greater effectiveness. ABSTRAKPenelitian ini bertujuan untuk mengkaji implementasi media Canva dalam pembelajaran Aqidah Akhlak pada materi akhlak mahmudah sebagai upaya meningkatkan motivasi belajar siswa kelas IX di MTs Miftahul Ilmiyah Mojowetan Blora. Latar belakang penelitian ini berangkat dari adanya kesenjangan antara idealitas pembelajaran Aqidah Akhlak yang diharapkan mampu membentuk keimanan dan akhlak mulia dengan realitas di lapangan yang menunjukkan rendahnya minat dan keterlibatan siswa. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kasus, melalui wawancara, observasi, dan dokumentasi sebagai teknik pengumpulan data. Hasil penelitian menunjukkan bahwa penggunaan Canva memungkinkan guru menyajikan materi akhlak mahmudah dalam bentuk visual yang kreatif, interaktif, dan menarik seperti poster, infografis, serta presentasi digital. Implementasi ini terbukti meningkatkan motivasi belajar siswa, membuat suasana kelas lebih partisipatif, serta membantu internalisasi nilai-nilai Islami secara lebih efektif. Namun, penelitian juga menemukan adanya tantangan, antara lain keterbatasan kompetensi digital guru, akses perangkat yang belum merata di kalangan siswa, serta kendala teknis seperti jaringan internet yang kurang stabil. Di sisi lain, terdapat faktor pendukung berupa antusiasme guru, ketertarikan siswa terhadap media visual, dan dukungan fasilitas sekolah yang memungkinkan inovasi pembelajaran tetap berjalan. Implikasi penelitian ini menegaskan pentingnya pemanfaatan media digital, khususnya Canva, dalam mendukung pembelajaran aqidah akhlak yang lebih kontekstual dan sesuai dengan karakter generasi digital. Penelitian ini merekomendasikan adanya pelatihan guru secara berkelanjutan serta penyediaan sarana teknologi yang lebih memadai. Selain itu, penelitian lanjutan disarankan untuk memperluas kajian penggunaan Canva pada mata pelajaran aqidah akhlak serta mengombinasikannya dengan model pembelajaran inovatif berbasis teknologi yang lain agar hasilnya semakin optimal.